The competitiveness of Central European IT exporters: Can this sector attract Western investment? - Tomasz Mroczkowski; Erran Carmel; Nivien Saleh (Journal for East European Management Studies, 2003)
This essay reports the results of a survey of IT exporters from Poland, Hungary, Romania, Bulgaria and the Czech Republic. The survey identifies the key competitive advantages and disadvantages of Central European IT companies as they compete for outsourcing work in the US and Western European markets. The results of the survey are then interpreted in the context of data on the development of IT environments, markets and sector investment in the region. We find that unlike key competitors' governments the Central Europeans have not pursued policies of supporting their infant IT exporters, which are small and underinvested. The paper proposes a set of measures that should be taken if needed Western Investment is to start flowing into the export oriented IT sector. – – Die vorliegende Studie berichtet über die Ergebnisse einer Umfrage unter ITExporteuren aus Polen, Ungarn, Rumaenien, Bulgarien und der Tschechischen Republik. Die Umfrage streicht die massgeblichen Wettbewerbsvor- und -nachteile oseteuropäischer IT-Firmen heraus, die ins Spiel kommen, wenn sie um Outsourcing-Verträge konkurrieren. Die Ergebnisse der Umfrage werden dann im Zusammenhang mit Daten über den IT-Markt und der regionalen Investitionstätigkeit interpretiert. Im Gegensatz zu den Regierungen von Konkurrenznationen haben osteuropäische Regierungen es versäumt, ihre jungen IT-Exporteure zu unterstützen, die klein und finanzschwach sind. Diese Studie schlägt mehrere Massnahmen vor, die dem IT-Exportsektor Investitionen verschaffen können.
Keywords: 650; Information technology; outsourcing; business associations; policy advice; infant industry